Reactions of physicians in the state of São Paulo to the use of telemedicine during the SARS-CoV-2 pandemic: cross-sectional study - Amaral, José Luiz Gomes; Endrigo, Antonio Carlos; Malik, Ana Maria; Ogata, Alberto José Niituma; Assumpção Neto, Jorge Corrêa (São Paulo Medical Journal, 2022)
BACKGROUND: Telemedicine can be a component of integrated healthcare practices and its use is not a recent phenomenon around the world. In Brazil, its more widespread use began during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, through extraordinary authorization from the Brazilian Ministry of Health. OBJECTIVES: To describe some aspects of use of teleconsultation among a sample of physicians in the state of São Paulo during the SARS-CoV-2 pandemic. DESIGN AND SETTING: Cross-sectional study based on a survey conducted by the São Paulo Medical Association (Associação Paulista de Medicina, APM) on medical practice during the SARS-CoV-2 pandemic between December 18, 2020, and January 18, 2021. RESULTS: This survey generated responses from 2,052 physicians. Of these, 981 (47.8%) reported not practicing any form of telemedicine. Among those who reported practicing telemedicine, 274 (28.4%) reported not receiving remuneration directly for the attendance provided and 225 (23.3%) reported receiving remuneration equal to what they would have received from face-to-face consultations. Regarding the professional linkage of the physicians who undertook telemedicine attendance, the majority (499; 51.8%) only attended private patients. Regarding the resources used to provide telemedicine attendance, most of the respondents used specialized digital platforms (594; 61.6%), electronic health records (592; 61.4%) and electronic prescriptions (700; 72.6%). CONCLUSION: This study demonstrates that important issues such as professional remuneration, use of electronic platforms and medical records, ensuring data protection and relationships between physicians and other stakeholders still need to be better defined, in order to achieve the desired scale and reach the outcomes defined.